Leakage of dissolved organic carbon (DOC) from settled Skeletonema marinoi cells incubated in pressure and control tanks - Stief, Peter (In: Stief, Peter; Schauberger, Clemens; Becker, Kevin W; Elvert, Marcus; Balmonte, John Paul; Franco-Cisterna, Belén; Middelboe, Mathias; Glud, Ronnie N (2023): Effects of increasing hydrostatic pressure on sinking diatom aggregates [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.960357, 2023)
The effect of increasing hydrostatic pressure on the microbial degradation, the organic matter composition, and the microbiome of 'marine snow' particles was studied in laboratory incubation experiments. Model aggregates were produced from the diatom Skeletonema marinoi and the natural microbial community of surface seawater collected in the Kattegat. The aggregates were incubated individually in rotating pressure and control tanks to keep them suspended during 20-day incubations in the dark and at 3°C. In the pressure tanks, hydrostatic pressure was increased at increments of 5 MPa per day to finally reach 100 MPa. This pressure scheme simulates the descent of diatom aggregates from the surface ocean down into a 10-km deep hadal trench. In the control tanks, pressure was always left at atmospheric level. To answer the question, if the observed pressure-induced leakage of dissolved organic carbon (DOC) from S. marinoi occurs during pressurization or depressurization, 3 additional experiments were carried out: 1) S. marinoi suspended in seawater were rotated at 0.1 MPa for 24 h and then allowed to settle for 3 h. 2) S. marinoi suspended in seawater were rotated at 60 MPa for 24 h, then allowed to settle for 3 h, and then depressurized. 3) S. marinoi suspended in seawater were first allowed to settle for 3 h, then incubated without rotation at 60 MPa for 1 h, and then depressurized. At the end of each experiment, vertical profiles of diatom cell abundance and DOC were determined, which revealed during which phase of the pressure experiment S. marinoi was leaking DOC into the surrounding seawater.
Keywords: biological carbon pump; Deep sea; Diatom; Hadal trench; hydrostatic pressure; Laboratory experiment; lipids; marine carbon cycle; marine snow; microbial community; Pigments; Respiration